Caregiver rating of early childhood development: Reliability and validity of the ASQ-3 in rural Guatemala. (October 2021) - Colbert, Alison M.; Connery, Amy K.; Lamb, Molly M.; Bauer, Desiree; Olson, Daniel; Paniagua-Avila, Alejandra; Martínez, María Alejandra; Arroyave, Paola; Hernández, Sara; Mirella Calvimontes, D.; Bolaños, Guillermo A.; El Sahly, Hana M.; et al.
Abstract: Background: Although performance-based assessment of early childhood development is preferred, there are a number of limitations to this methodology in low resource settings (LRSs). Hence, clinicians and researchers often rely on caregiver report screening tools. The Ages and Stages Questionnaire 3 (ASQ) is one of the most widely used caregiver report measures globally. Adequate psychometric properties have been demonstrated in high income settings, especially when used in older children, high- risk children, or those with severe neurodevelopmental delays. However, its utility is more variable within very young children and for use in LRSs. Methods: The reliability and validity of the ASQ was determined for children ages 0–5 years living in rural Guatemala. Internal consistency and test-retest reliability were assessed, as well as concurrent and predictive validity. Sensitivity, specificity, positive and negative predictive values related to performance-based developmental assessment (Mullen Scales of Early Learning; MSEL) and growth status (i.e. stunting) were also calculated. Results: Internal consistency reliability for the ASQ was adequate, except when results were limited by small sample size. Test-retest reliability ranged from low to moderate ( r  = 0.08–0.43; p  < 0.05–0.01). However, there was significant variability in mean scores over time across ASQ domain scores. In terms of validity, the ASQ did not discriminate adequately between children who performed within or below age-expectations on performance-based developmental testing or those with and without stunting. Conclusions: The ASQ did not demonstrate adequate psychometric properties in rural Guatemala, consistent with concerns documented in other LRSs. These results indicate that existing caregiver report screening measures of early childhood development should be utilized with caution in LRSs, and alternative methods for assessment or in the development and utilization of caregiver report measures should be considered. Highlights: There are barriers to testing of developmental skills in Low Resource Settings and obstacles result in reliance on caregiver report screening measures. Ages and Stages Questionnaire-3 is a widely utilized caregiver report screening measure. Studies reports concerns about ASQ use other cultures or non-English speaking populations In rural Guatemala, weak psychometric properties of the ASQ identified. Results highlight challenges of reliance on caregiver report and use of screening measures.